Dewi Kurniawati ANALISIS KEPUASAN KONSUMEN TERHADAP PELAYANAN RESTORAN PERGURUAN TINGGI DENGAN METODE QUALITY FUNCTION DEPLOYMENT (QFD) (STUDI DI RESTO KEMUNING POLIJE) - Kurniawati, Dewi; Oktanita Jaya Anggraeni; R. Abdoel Djamali; Naning Retnowati; Rizal Perlambang CNAWP (Jurnal Ilmiah Inovasi, 2024)
Research to understand consumer needs and plan strategic service quality improvements. The research method used is descriptive quantitative by collecting data through questionnaires to 100 respondents who meet certain criteria. Data was analyzed based on five SERVQUAL dimensions: reliability, responsiveness, assurance, empathy, and tangibles. The research results show that the average gap in the five SERVQUAL dimensions is positive, indicating a good level of customer satisfaction, but still requires improvement in several aspects, such as the number of employees, responses to complaints, and payment systems. Importance Performance Analysis (IPA) analysis identifies priority attributes that must be improved, while House of Quality (HOQ) analysis produces improvement strategies, including the implementation of a modern payment system, employee training, and the provision of supporting facilities. This research concludes that structured and continuous service improvements are needed to increase consumer satisfaction and business competitiveness. Strategic recommendations are provided to support the sustainability of Resto Kemuning Polije in facing competition in the service industry.